The Role of the Educational Programs in the Improving of Confidence in Vaccination against Pneumococcal Infection among Population - N I Briko; V A Korshunov; A Ya Mindlina; R V Polibin; A V Shamis; A G Saltykova (Эпидемиология и вакцинопрофилактика, 2022)
Relevance. Pneumococcal disease is a common cause of morbidity and mortality in adults and children worldwide. Vaccination against pneumococcal infection was included in the National Immunization Schedule in the Russian Federation in 2014. But despite the progress made, the proportion of children who received a completed course of vaccination remains insufficient. Coverage of the adult population remains low. A significant role in this is played by confidence of the population to vaccination against pneumococcal infection. In this regard, we conducted a study to assess the effectiveness of the educational programs in the improving of confidence in vaccination against pneumococcal infection among various target groups of population. Materials and methods. The results of the developed and conducted educational campaigns, consisting of two stages, were used as material: a series of face-to-face events for young people (students of non-medical universities in Moscow) and a series of webinars for medical professionals of various specialties. In the first stage of the educational component, the total coverage of the target audience («future parents») amounted to 650 people. Face-to-face events were held with the participation of students from Sechenov University using the peer-to-peer approach. The total audience of the second phase of the educational component (a series of 5 webinars for health professionals) was more than 3,000 people (2,902 connections, some of them group). Online events for medical workers were held by leading experts in the field of epidemiology and vaccine prevention, psychology. Evaluation of the effectiveness of the campaign was carried out through measurements (surveys before and after the event). To assess the statistical significance of differences, Pearson's Chi2 test was used at the accepted level of statistical significance p < 0.05. Qualitative variables are presented as proportion and 95% confidence interval of the proportion. Statistical processing was performed using IBM SPSS Statistics v.20.0, data visualization – Microsoft Excel 2016. Results. The proportion of students who have a positive attitude towards vaccination increased by 16% – from 41.0±5.6% to 57.0±6.0%, p<0.05. The level of awareness about the availability of vaccination against pneumococcal infection increased by 75.9% – from 21.2 ± 4.5% in the initial survey to 97.1 ± 2.0% in the final one (p < 0.001). Awareness about contingents subject to vaccination against pneumococcal infection increased by 78% (the proportion of respondents who initially found it difficult to answer this question decreased from 85.3 ± 3.9% to 7.2 ± 3.1% (p < 0.001). The total audience of the second stage of the educational component (a series of 5 webinars for medical professionals) amounted to more than 3000 people (2902 connections, some of them were group). The proportion of doctors willing to recommend vaccination against pneumococcal infection increased from 82.1 ± 1.4% to 97.0 ± 0.6%, p < 0.001. Conclusion. Educational programs plays important role in the improving confidence in vaccination both among medical workers and among the population. Short-term indicators of the effectiveness of the event can be reflected in the increased awareness of participants in the issues of vaccination and infectious diseases. At the same time, a significant change in the indicator of attitudes towards vaccination should be expected when conducting a series of educational events using various formats – lectures, conversations, discussions, interactive games.